PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA BALAI PENGELOLA TRANSPORTASI DARAT KELAS II SUMATERA SELATAN - Selva Dwi Utary; Edduar Hendri; Suhada Suhada (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to test the hypothesis of the influence of Communication and Work Environment on Job Satisfaction. The method used in this research is a quantitative method with a total sample of 69 respondents. The data analysis techniques used in this study are multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test, and F-test using SPSS software. The results of the t-test show a significant value of 0.000 < 0.05 (5%), thus Ha is accepted and Ho is rejected. Communication and Work Environment each have a significant partial effect on Job Satisfaction at the Class II South Sumatra Land Transportation Management Office. The results of the F-test conclude that there is a significant simultaneous influence of Communication and Work Environment on Job Satisfaction at the Class II South Sumatra Land Transportation Management Office. Keywords: Communication, Work Environment, and Job Satisfaction